2016
DOI: 10.1111/wej.12221
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficiencies of sludge dewatering and domestic wastewater treatment by using the bioflocculant from rice stover

Abstract: Potential of a bioflocculant from rice stover was studied in sludge dewatering and domestic wastewater treatment. Production of this bioflocculant showed good correspondence to cell growth, after fermentation for 60 h, the fermentation liquor was obtained, from 1.0 L of which a value of 2.37 g bioflocculant can be extracted, and the main backbone of this bioflocculant was polysaccharides. Without adjusting the sludge's initial pH value of 6.5, when incubated with 18 mg/L of this bioflocculant, dry solids (DS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…This information was similar to that reported by Wang et al, while a different biopolymer component (mainly protein) was reported by Peng et al The different nutrition components and biophysical environments may account for the discrepancy in biopolymer components. Gel permeation chromatography indicated that the approximate molecular mass of the BF-ADSW was 4.21 × 10 5 Da, a relatively high molecular mass, compared to those of the biopolymers produced by Aspergillus flavus and Rhodococcus erythropoli. , The higher molecular mass, the greater the number of adsorption points and the stronger the bridging ability supplied to the sludge particles. , Furthermore, the ζ potential of the BF-ADSW was determined to be 13.2 mV, a positive charge that can effectively combine with a negative sludge particle, which further enhanced the sludge dewatering.…”
Section: Resultsmentioning
confidence: 98%
“…This information was similar to that reported by Wang et al, while a different biopolymer component (mainly protein) was reported by Peng et al The different nutrition components and biophysical environments may account for the discrepancy in biopolymer components. Gel permeation chromatography indicated that the approximate molecular mass of the BF-ADSW was 4.21 × 10 5 Da, a relatively high molecular mass, compared to those of the biopolymers produced by Aspergillus flavus and Rhodococcus erythropoli. , The higher molecular mass, the greater the number of adsorption points and the stronger the bridging ability supplied to the sludge particles. , Furthermore, the ζ potential of the BF-ADSW was determined to be 13.2 mV, a positive charge that can effectively combine with a negative sludge particle, which further enhanced the sludge dewatering.…”
Section: Resultsmentioning
confidence: 98%
“…The water molecule and sludge particles are closely connected such that the sludge particles form a stable colloidal suspension [9]. This characteristic hinders the separation of mud and water, and the performance of direct sludge dewatering is poor [10]. Therefore, sludge conditioning before sludge dewatering is particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Sludge dewatering is one of critical steps in sludge treatment as it reduces signi cant water from the mixed sludge which creates favorable conditions for next sludge treatment process. Studies on dewatering enhancement have been done quite a few and mostly with sewage sludges from WWTPs; such as using chemicals (Guo et al 2016 Addition of agro-wastes for dewatering enhancement has also been paid much attention from researchers within the past decade (Liang et al 2018;Wójcik 2019;Guo et al 2019). This approach is considered attractive as it is quite environmentally friendly, energy saving, and the waste-blended sludge can be reused as great potential materials for composting, or post-treatment by incineration.…”
Section: Introductionmentioning
confidence: 99%